Development and Validation of Chronopotentiometric Method for Imidacloprid Determination in Pesticide Formulations and River Water Samples - Ana Đurović; Zorica Stojanović; Snežana Kravić; Nada Grahovac; Vojislava Bursić; Gorica Vuković; Zvonimir Suturović (International Journal of Analytical Chemistry)
A new electrochemical method for determination of imidacloprid using chronopotentiometry on thin film mercury and glassy carbon electrode was presented. The most important experimental parameters of chronopotentiometry were examined and optimized with respect to imidacloprid analytical signal. Imidacloprid provided well-defined reduction peak in Britton-Robinson buffer on thin film mercury electrode at −1.0 V (versus Ag/AgCl (KCl, 3.5 mol/L)) and on glassy carbon electrode at −1.2 V (versus Ag/AgCl (KCl, 3.5 mol/L)). The reduction time was linearly proportional to concentrations from 0.8 to 30.0 mg/L on thin film mercury electrode and from 7.0 to 70.0 mg/L on glassy carbon electrode. The detection limits were 0.17 mg/L and 0.93 mg/L for thin film mercury and glassy carbon electrode, respectively. The estimation of method precision as a function of repeatability and reproducibility showed relative standard deviations values lower than 3.73%. Recovery values from 97.3 to 98.1% confirmed the accuracy of the proposed method, while the constancy of the transition time with deliberated small changes in the experimental parameters indicated a very good robustness. A minor influence of possible interfering compounds proved good selectivity of the method. Developed method was applied for imidacloprid determination in commercial pesticide formulations and river water samples.